A fluorescent probe for hypochlorite based on the modulation of the unique rotation of the N–N single bond in acetohydrazide1. Issue 52 (4th July 2015) - Long, Lingliang; Wu, Yanjun; Wang, Lin; Gong, Aihua; Hu, Feilong; Zhang, Chi
<x xml:space="preserve">Abstract</x> A fluorescent probe for hypochlorite was developed based on a novel signaling mechanism of modulating the N–N bond rotation in acetohydrazide.